Improvement of functional neurological disorder after administration of esketamine nasal spray: a case report - Júlia Vendrell-Serres; Óscar Soto-Angona; Amanda Rodríguez-Urrutia; Gara Arteaga-Henríquez; Josep A. Ramos-Quiroga (SAGE Publishing, 2021)
Functional neurological disorder (FND) is a complex neuropsychiatric condition characterized by the presence of neurological symptoms and signs (either motor or sensory) that cannot be explained by any known medical or mental disease. It is frequently presented with psychiatric comorbidities, such as major depression. Its prognosis is poor, with low improvement or recovery rates at 1 year after their onset, and no particular treatment has demonstrated significant efficacy in this regard. Here, we describe the management of a patient affected by treatment-resistant depression (TRD) and FND characterized by mixed paralysis (sensory and motor) in the left arm, and who was successfully treated with esketamine nasal spray, achieving remission in both disorders. The US Food and Drug Administration and the European Medicines Agency recently approved esketamine, the S-enantiomer of ketamine, for treatment of TRD. It is a fast-acting drug that provides a rapid-onset improvement of depressive symptoms. We have presented the first case, to our knowledge, of functional neurological symptoms being successfully treated with esketamine in a patient with comorbid TRD. While the novelty of this data implies a clear need for further research, it is suggested that esketamine might be a useful tool for the treatment of FND, acting through different theorized mechanisms that are in tune with recent advances in knowledge of the etiopathology of FND.